Generation and characterization of Wolbachia transinfections and development of female-specific RIDL technology in Aedes albopictus - Blagrove, M (2014)
Aedes albopictus is an important vector of dengue and chikungunya viruses, and, over recent decades, has resisted traditional control strategies allowing it to spread from its native Southeast Asia throughout the world. In this thesis, two alternative control methods are assessed and developed: transinfection with the inherited bacteria Wolbachia, for population replacement with a refractory strain; and a genetic equivalent to the sterile insect technique, RIDL (Release of Insects carrying a Dominant Lethal), for population suppression. Wolbachia is a genus comprising maternally inherited intracellular α-proteobacteria which primarily infect arthropods. Certain strains of Wolbachia both have the ability to manipulate host reproduction through cytoplasmic incompatibility (CI) which allows Wolbachia to invade host populations by conferring a reproductive advantage on infected females, and have been shown to confer broad-spectrum pathogen resistance on their hosts. Here, a transinfection of wMel in Aedes albopictus (Uju.wMel) was generated which shows complete bidirectional CI with the natural Wolbachia infection of Ae. albopictus, in the absence of any major fitness costs and (as shown by collaborators) completely abolishes dengue and chikungunya virus transmission. It was also shown that the pathogen inhibition in Uju.wMel occurs in the absence of immune stimulation. Evidence supporting cholesterol sequestration by wMel as a mechanism for the pathogen inhibition observed in Uju.wMel was found. Previous attempts to produce a conditionally inviable genetic sexing Ae. albopictus RIDL line have resulted in a sub-optimal strain in which the construct was not sufficiently specific or repressible, resulting in a high proportion of off-target inviable mosquitoes. Here, the mating competitiveness of RIDL males was shown to be not significantly different from wild-type, confirming the potential utility of the system. Multiple truncations of the promoter were made in an attempt to reduce the off-target expression.